Peningkatan Kapabilitas Manajemen Keuangan Wirausahawan melalui Pelatihan Analisis Keuangan di Provinsi Gorontalo - Ardiyanto Saleh Modjo (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2024)
The province of Gorontalo holds significant potential for entrepreneurial development due to its abundant natural resources. However, entrepreneurs in this region often face challenges in financial management, which negatively impacts the growth of their businesses. This training aims to enhance the financial management capabilities of entrepreneurs in Gorontalo through a financial analysis training program. The methodology involved the identification of target areas and participants, the preparation of training materials, and the implementation of the training through offline sessions. The training was attended by 20 participants, consisting of 15 officials from the provincial cooperative and industry office and 5 local entrepreneurs. The results indicate that the training successfully improved the participants' understanding and skills in managing their business finances. Evaluation of the four participant groups showed that 75% achieved very good scores, with an overall average score of 89. These findings suggest that the training program effectively enhanced the participants' financial literacy and financial analysis skills, which is expected to contribute to the sustainable growth of businesses in the Province of Gorontalo.